Does international law proscribe coups d'état? Africa's role in the development of the proscription - Ruwitah, Mduduzi Aviton (Department of Public Law, 2021)
Coups d'état have occurred around the world since time immemorial but have been more commonplace amongst African states. They have typically yielded bloodshed and instability and, they inevitably culminate in the gross violation of the most basic human rights. They also arguably constitute a perennial threat in the politics of African states and, they have been condemned in numerous instances. Such condemnation brings to the fore, questions as to international law's position on coups d'état. In light of International law placing a high premium on the doctrine of national sovereignty, it is tempting to conclude that coups d'état are beyond the scope of international law thus not being proscribed. This position is further strengthened by the absence of international treaties/conventions proscribing coups d'état. It can, however, be argued that the recognition given to the notion of democracy by some treaties/conventions such as the UDHR, CEDAW, and ICCPR, may amount to an implicit proscription of coups d'état under international law. There is also, a right to democracy, along with a proscription of coups d'état under customary international law as reflected by state practice. African states, being specially affected by the scourge of coups d'état, have played a leading role in the development of the customary international law proscription of coups d'état. Regardless of it being difficult for state responsibility to ensue, coups d'état constitute wrongful acts at international law.